Polio žmogaus ugdymas ir tradicija Faidro kalboje (Symp. 178 a–180 b) - Ališauskas, Vytautas (Literatūra, 2015)
Phaedrus’ speech in Plato’s Symposium was often ignored by Platonic scholars as unphilosophical, and has been analysed mostly in its rhetorical aspects. This narrowed the intentions of the dialogue down to theoretical speculations, neglecting a practical problem – namely, which values of the Greek polis remained relevant in the epoch of radical cultural transformation through which Plato lived. The detailed analysis of Phaedrus’ speech reveals some of its aspects that remained latent until now, establishing that the system of concepts of ‘shame’ and ‘aspiration to glory’ derives from the traditional system of values of Greek military community, and thus has a concrete historical and social content. It was precisely Socrates and later Plato who embarked on the revision of the Greek concept of ‘shame’ (as Plato’s Apology attests). The paper employs additional sources that help to recreate the historical context of the speech and to inscribe it into its authentic Sitz im Leben. Furthermore, Lysias’ speech against Alcibiades is linked with Phaedrus’ speech and the whole context of the Symposium.